Association between intraoperative ventilator settings and plasma levels of soluble receptor for advanced glycation end‐products in patients without pre‐existing lung injury. Issue 7 (29th June 2015) - Jabaudon, Matthieu; Futier, Emmanuel; Roszyk, Laurence; Sapin, Vincent; Pereira, Bruno; Constantin, Jean‐Michel
Abstract Background and objective The soluble form of the receptor for advanced glycation end‐products (sRAGE) is elevated and correlated with severity in patients with acute respiratory distress syndrome (ARDS). The impact of ventilator settings on plasma levels of sRAGE, in patients with or without pre‐existing lung injury, remains under‐investigated to date. Our objective was to assess the effects of a lung‐protective ventilation strategy (combining low tidal volume, positive end‐expiratory pressure and recruitment maneuvers), as compared with a non‐protective approach (with high tidal volume and zero end‐expiratory pressure), on plasma levels of sRAGE in patients without lung injury undergoing major abdominal surgery. Methods Plasma samples were obtained from 95 patients enrolled in a large randomized controlled trial of lung‐protective ventilation for major abdominal surgery. Plasma levels of sRAGE were measured in duplicate with an enzyme‐linked immunoassay on day 1, immediately after surgery, and on postoperative days 1, 3 and 7. Results Early postoperative plasma levels of sRAGE were significantly lower in the lung‐protective ventilation group (n = 47) than in the non‐protective ventilation group (n = 48) (mean (standard deviation), 1782 (836) vs 2171 (1678) pg/mL, respectively, P = 0.03). Intraoperative changes in plasma sRAGE were associated with postoperative hypoxemia and ARDS. Conclusions A lung‐protective ventilation strategy decreased plasma sRAGE in patients without lung injury undergoing major abdominal surgery compared with the patients with non‐protective ventilation. This intraoperative decrease could reflect a lesser degree of epithelial injury.